Assembling carbon fiber–graphene–carbon fiber hetero-structures into 1D–2D–1D junction fillers and patterned structures for improved microwave absorption. (3rd March 2017) - Li, Huimin; Liu, Lin; Li, Hai-Bing; Song, Wei-Li; Bian, Xing-Ming; Zhao, Quan-Liang; Chen, Mingji; Yuan, Xujin; Chen, Haosen; Fang, Daining
Abstract: Since carbon-based structures of various dimensions, including one-dimensional (1D) carbon nanotubes, two-dimensional (2D) graphene and three-dimensional (3D) carbon foams, have attracted significant attention as microwave absorption fillers, we present an exceptional hetero-junction filler with a 1D–2D–1D feature, achieved by manipulating 2D graphene into 1D carbon fibers in the fiber-extruding process under the electric field. The as-fabricated 1D–2D–1D structural fillers exhibited much-improved dielectric properties and promoted microwave absorption performance in their composites, which is linked to the establishment of enhanced polarization capability, the generation of increased electric loss pathway and the creation of more favorable electromagnetic energy consumption conditions. The results suggest that employing 2D graphene in the 1D–2D–1D nanostructures played the critical role in tuning the electromagnetic response ability, because of its intrinsic electric advantages and dimensional features. To broaden the effective absorption bandwidth, periodic pattern-absorbing structures were designed, which showed combined absorption advantages for various thicknesses. Our strategy for fabricating 1D–2D–1D structural fillers illuminates a universal approach for manipulating dimensions and structures in the nanotechnology.